Back‐to‐Back Screen‐Printed Electroanalytical Sensors: Extending the Potential Applications of the Simplistic Design. Issue 10 (15th July 2015) - Ruas de Souza, Ana P.; Bertotti, Mauro; Foster, Christopher W.; Banks, Craig E.
Abstract In our previous paper (Analyst, 2014, 139, 5339) we introduced the concept of the back‐to‐back electrochemical design where the commonly overlooked back of screen‐printed electrodes are utilised to provide electroanalytical enhancements in screen‐printed electroanalytical sensors. In this configuration the overall sensor comprises of a flexible polyester substrate which has a total of two working, counter and reference electrodes present on the sensor, with a set of electrodes on each side of the substrate. The sensors are designed to allow for a commonly shared electrical connection to the potentiostat and do not require any specialised connections. In this paper we demonstrate proof‐of‐concept extending the electroanalytical utility of the back‐to‐back screen‐printed electrode sensors to bulk modified single‐walled carbon‐nanotubes and electrocatalytic cobalt phthalocyanine microband electrodes. The electroanalytical applications of these novel electrode configuration are exemplified towards the sensing of dopamine, capsaicin and hydrazine. This paper demonstrates the versatility of the back‐to‐back configuration where different surface modifications can be readily employed giving rise to enhancements in sensor performance.